TECHNICAL EFFICIENCY IN PADDY RICE PRODUCTION IN NIGER DELTA REGION OF NIGERIA. (2014) - Eze, F. A.; C.C, C.C; Orebiyi, Orebiyi; Lemchi, J. S;; I, J.; Ohajianya, Ohajianya; O, D.; Nwaiwu, Nwaiwu; U, I.
No abstract available